Substrat i superstrat en l'evolució del català - Moran i Ocerinjauregui, Josep (Caplletra. Revista Internacional de Filologia, 1999)
Reflections on the significance of substratum and superstratum in the genesis and evolution of Catalan. The author considers how the recourse to the pre-Roman susbtratum in the etymological interpretation or in the historical and critical grammar has been carried to excess both by those absolutely against it and by those who take it as an all-explaining panacea. He also points out that, conversely to the interest in substratum, the Germanic superstratum has not received the attention it deserves in the genesis of Catalan because of various prejudices, some of them of an ideological kind.